(untitled) (Journal of Bangladesh Academy of Sciences, 2026)
A number of 5-substituted isatin derivatives (2–6) were synthesized from Nbenzylisatin (1) by multistep organic reaction. Bromination of isatin followed by Suzuki-Miyaura coupling reaction with commercially available organoboron reagents afforded the compounds 2–6 with moderate yield. All the compounds were characterized using different spectroscopic techniques and their cytotoxicity was studied by brine shrimp lethality bioassay. Among these compounds, 2, 3, 5, and 6 showed moderate cytotoxicity with LC50 values 54.0, 76.5, 58.3, and 76.3 μg/mL, respectively, whereas compound 4 showed significant cytotoxicity with an LC50 value of 33.2 μg/mL. Structural modifications significantly affected electronic energy, dipole moment, and charge distribution. Compound 6 showed the highest dipole moment, suggesting greater polarity and potential intermolecular interaction capability. Frontier molecular orbital analysis identified compound 4 as the most reactive analogue, characterized by the lowest HOMO-LUMO energy gap, lowest hardness, and highest softness. J. Bangladesh Acad. Sci. 50(2); 247–257: June 2026